Nourishing a healthy future: The role of irrigation in a changing world - Hamilton, Christine; Lefore, Nicole; Ringler, Claudia; Barron, Jennie (Irrigation Association, 2025)
The 2025 lecture, delivered by Claudia Ringler, PhD, explored the critical role of irrigation in advancing global food security — a timely topic given Nebraska’s leadership in irrigation innovation. With changing weather patterns and growing demand for water resources, smart irrigation technologies are becoming a game-changer in securing food and better diets. Such innovations are critical amid nutrition and health crises.